Usages gouvernementaux de la participation citoyenne au Chili : mobiliser, contrôler, légitimer (1964-2010) - Nicolas Pinet (L'Ordinaire des Amériques)
This article analyzes the Chilean rulers’ representations of public participation through their discursive and public policy uses. Can we explain their ambivalent relations with public participation –being both the source of their legitimacy and a threat to their power– by historical situations and political personalities? Or is it rather a structural effect of democratic institutionnality? To answer, the analysis deals successively with the Eduardo Frei Montalva (1964-1970), Salvador Allende (1970-1973) and Concertation (1990-2010) governments. It appears that, despite opposite situations, the successive rulers share a similarly instrumental relation with public participation as they need it either to achieve their political goals –first and second cases–, or to reassert their own legitimacy, as well as the democratic institutions’ –third case.